Analisis Kelayakan Bisnis Property (Studi pada Perumahan Natura Residence Cluster Natura Regency Jombang) - Vindi Nur Maharani; Sonny SM Laksono (Universitas Islam Kadiri, 2022)
This research discusses the feasibility analysis of the property business in the Natura Residence Cluster Natura Regency Jombang. This research aims to determine the feasibility of the housing business in the perspective of financial aspects supported by non-financial aspects. This research is a descriptive research by using mixed research methods with a concurrent embedded strategy. Data processing uses linear and hierarchy techniques for qualitative analysis which includes legal aspects, technical/operational aspects, management/organizational aspects, social-economic aspects, environmental impact aspects, while quantitative analysis uses linear time series methods for market-marketing and capital budgeting aspects. for the financial aspect. The results of data processing indicate that the Non-Financial Aspects and Financial (Financial) Aspects of the Natura Residence Cluster Natura Regency Housing Project can be said to be feasible to continue by considering various factors that can affect the success or failure that can be anticipated.